Analisis Multi-Kriteria dengan Pendekatan Analytical Hierarchy Process Untuk Strategi Mitigasi dan Adaptasi Bencana Banjir di Distrik Nabire Kabupaten Nabire - Husain Husain; Johnson Siallagan; Janviter Manalu; Auldry F. Walukow; Basa T. Rumahorbo (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Nabire Regency, Central Papua Province, has a high vulnerability to flooding due to significant rainfall intensity. Risk analysis was conducted using the Analytical Hierarchy Process (AHP) method to determine the priority of factors causing flooding, including hydrological aspects, land use, infrastructure, and socio-economic impacts in a systematic manner. The results of this study indicate that the analysis of public perception of flooding disasters was conducted by modeling data using a Likert scale, which was processed computationally to generate patterns of public perception. The Analytical Hierarchy Process (AHP) method was used to determine the priority of data-based mitigation strategies. The results confirm that BPBD plays a dominant role in flood risk management through the integration of adaptive and sustainable environmental information systems.